Cardiac Effects of Treadmill Running at Different Intensities in a Rat Model - Yan, Zhipeng; Zeng, Ni; Li, Jieting; Liao, Tao; Ni, Guoxin (Frontiers in Physiology, 2021)
Purpose: Exercise is an effective intervention for both the prevention and treatment of cardiovascular diseases. In this study, we investigated the structural and functional changes that occur in cardiac response and how they diﬀer with various exercise intensities, hence exploring the potential signal transduction. Methods: Male Sprague–Dawley rats were randomly divided into the sedentary (SED), low-intensity running (LIR), medium-intensity running (MIR), and high-intensity running (HIR) groups. Each exercise group had 3 different operation time subgroups for 1, 4, and 8 weeks, respectively, and all rats observed a daily 1 h treadmill routine 5 days per week. Echocardiographic measurements were performed at the end of the experimental program. Additionally, myocardium samples and blood were collected for histological and biochemical examinations. Changes in the extracellular signal-regulated kinases 1/2 (ERK1/2) signal pathway were detected by Western blotting. Results: After a week of running, ventricular myocyte size and the phosphorylation of ERK1/2 increased in the HIR group, while left ventricular (LV) diastolic diameter values and LV relative wall thickness increased in the LIR and MIR groups. In addition, we observed heart enlargement, cTnI decrease, and ERK1/2 signal activation in each of the exercise groups after 4 weeks of running. However, the HIR group displayed a substantial rupture and increased fibrosis in myocardial tissue. In addition, compared with the LIR and MIR groups, 8 weeks of HIR resulted in structural damage, fiber deposition, and increased cTnI. However, there was no difference in activation of ERK1/2 signaling between the exercise groups and SED group. Conclusions: The effect of running on cardiac hypertrophy was intensity dependent. In contrast to LIR and MIR, 8 weeks of HIR-induced cardiac hypertrophy was characterized by potential cardiomyocyte injury, which increased the risk of pathological development. Furthermore, the ERK signaling pathway was mainly involved in the compensatory hypertrophy process of the myocardium in the early stage of exercise and was positively correlated with exercise load. However, long-term exercise may attenuate ERK signaling activation.